Global Banking, Trade, and the International Transmission of the Great Recession. Issue 623 (16th May 2019) - Born, Alexandra; Enders, Zeno
Abstract: We employ a dynamic stochastic general equilibrium model to investigate the transmission of the global financial crisis via the collapse of export demand (trade channel) and through losses on cross-border asset holdings (financial channel). Calibrated to German data, the model predicts the trade channel to be twice as important as the financial channel. In the United Kingdom, the latter dominates due to higher foreign-asset holdings, which, at the same time, serve as an automatic stabiliser in case of plummeting foreign demand. The financial channel leads to much longer-lasting effects. Stricter enforcement of bank capital requirements would have frontloaded the recession.